Enhances in Crude Protein and Effects on Fermentation Profile of Corn and Forage Sorghum Silage with Addition of Cowpea. Issue 1 (22nd June 2013) - Contreras‐Govea, Francisco E.; VanLeeuwen, Dawn M.; Angadi, Sangu V.; Marsalis, Mark A.
Abstract : This study was conducted to assess nutritive value of corn ( Zea mays L.) and forage sorghum [ Sorghum bicolor (L.) Moench] silage when ensiled with different proportions of cowpea [ Vigna unguiculata (L.) Walp.]. Corn and forage sorghum were harvested at the ½ milk line and late dough stages of kernel maturity, respectively, and cowpea was harvested at a vegetative stage in two consecutive years at New Mexico State University (NMSU), Agricultural Science Center at Clovis. All three crops were chopped using a conventional chopper. The main crops, corn and forage sorghum, were mixed with cowpea at main crop:cowpea ratios of 100:0, 75:25, 50:50, 25:75, and 0:100%. For each mixture, 1.1 lb of fresh material was vacuum sealed in a plastic bag and fermented for an average of 127 days, four bags per mixture. In both crops, crude protein (CP) increased as proportion of cowpea increased in the mixture. In addition, pH, lactic acid, and total acids increased in both crops when cowpea was added. Silage with 100% cowpea had the highest pH and lowest lactic acid concentration. It is concluded that mixing cowpea with corn and forage sorghum for silage increased CP concentration of the mixture. Additional research is needed to assess mixtures that produce silage with more desirable fermentation characteristics.